2022
DOI: 10.1371/journal.pntd.0010437
|View full text |Cite
|
Sign up to set email alerts
|

Entomological risk of African tick-bite fever (Rickettsia africae infection) in Eswatini

Abstract: Background Rickettsia africae is a tick-borne bacterium that causes African tick-bite fever (ATBF) in humans. In southern Africa, the tick Amblyomma hebraeum serves as the primary vector and reservoir for R. africae and transmits the bacterium during any life stage. Previous research has shown that even when malaria has been dramatically reduced, unexplained acute febrile illnesses persist and may be explained by the serological evidence of rickettsiae in humans. Methodology/Principal findings We collected 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Prior studies indicate that 83% of reported cases involve individuals aged between 18-64 years, 15% were 65 or older, and 2% were between 0-17 years [2]. As the primary tick-borne rickettsiosis and second most common cause of acute febrile illness after malaria in travelers returning from sub-Saharan Africa [3,4], African tick bite fever must be considered in the differential diagnosis for travelers returning from endemic areas.…”
Section: Case Discussionmentioning
confidence: 99%
“…Prior studies indicate that 83% of reported cases involve individuals aged between 18-64 years, 15% were 65 or older, and 2% were between 0-17 years [2]. As the primary tick-borne rickettsiosis and second most common cause of acute febrile illness after malaria in travelers returning from sub-Saharan Africa [3,4], African tick bite fever must be considered in the differential diagnosis for travelers returning from endemic areas.…”
Section: Case Discussionmentioning
confidence: 99%
“…The global incidence rate of human rickettsiosis caused by R. africae has been reported to be above 5% among travelers who developed an acute febrile infection after their return from sub-Saharan Africa [ 24 ]. The presence of R. africae from A. hebraeum and species of Haemaphysalis and Rhipicephalus has long been established in South Africa [ 20 , 23 , 28 ]; hence South Africa has been described as an endemic region for ATBF.…”
Section: Discussionmentioning
confidence: 99%
“…They are threehost hard ticks (where each life stage completes a blood meal on a particular host before dropping off and ecdysis), they are vividly coloured (especially the males). ATBF is second only to malaria as the cause of acute febrile illness in travelers returning from sub-Saharan Africa (Freedman et al, 2006), and R. africae seropositivity rate (which is indicative of past infection) is high in indigenous populations from rural areas and could reach 60 to 90% (Ledger et al, 2022). The Rickettsia genus includes 25 validated species, 17 of which are proven human pathogens.…”
Section: Distribution Of the Disease In Sub-saharan Africa And The Ea...mentioning
confidence: 99%